Entrepreneurs and the Social and Economic Dynamics of a Small Brazilian Community. (2017) - Sant'Anna, Anderson de Souza; Nelson, Reed Elliot
Abstract: In this paper, we attempt to study the relation between variance among entrepreneurs and the social and economic dynamics of a small Brazilian community that over a comparatively short period emerged from abandonment and obscurity to become one of the premier tourist destinations in the country. Although our study was unabashedly exploratory, inspired on the Grounded Theory method, we encountered several accounts reflecting the literature in our initial interviews. Some viewed the town's recent development as the result of the inspired intervention of a few prominent leaders while some viewed the town's trajectory as a straightforward result of macroeconomic evolution. The importance of variance among entrepreneurs and their relations among themselves and with the broader community became more apparent and we found a modest body of work that helped us to interpret our results and which we in turn will attempt to inform. We will explore our results and their likely relationship to existing theory, but for introductory purposes we preview six major findings: (1) The community has developed a shared vocabulary of oppositional categories which express the major social tensions created by the town's rapid development; (2) different entrepreneurial postures or types are located in different spaces created by the intersection or juxtaposition of these oppositional categories. the different types are aware of their location and the location of others in this positional scheme; (3) different types of entrepreneurs have different goals and preferences for the development of the community, which have radically different implications for the long term nature of the community; (4) the distribution of different types of entrepreneurs has an impact on the economic and social dynamics of the community; (5) the types of entrepreneurs identified by the community's cognitive system overlap but do not duplicate existing typologies in the entrepreneurship literature.